Analisis Wacana Kritis Dukungan Peran Selebritis Pada Pemilihan Calon Presiden 2024 Prabowo Subianto Melalui Instagram @Prabowosubianto - Prakoso, Jatayu Hadi; Santoso, Ade Budi; Wijayanti, Isa; Romadon, Saiful (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Communication plays an important role in human life, and in Indonesia, the presidential election is an important event where citizens elect the president and vice president directly. Prabowo Subianto, a well-known figure in the world of Indonesian politics, has received support from various celebrities and content creators. This research aims to look at persuasive communication to convince other people to change their attitudes or behavior regarding an issue. The research method used in this research is qualitative and focuses on critical discourse analysis to reveal the strengths inherent in each linguistic process. The main data source for this research is Prabowo Subianto's Instagram account, which actively posts his activities, including activities with celebrities. influencers, and public figures. One of the artists who is part of TKN Prabowo-Gibran is Raffi Ahmad, Nagita Slavina. There are also other artists involved, such as Verrel Bramasta. The use of celebrities is a strategy to attract attention and get votes from voters. The results of this research, namely persuasive communication, play an important role in presidential elections. Celebrity endorsements can influence people's perceptions and voting behavior. Prabowo Subianto's Instagram account is a rich source of data that reveals the power inherent in every linguistic process, and critical discourse analysis is an effective method for analyzing such discourse. A text, conversation and others are forms of certain ideological practices, ideologies built by dominant groups with the aim of reproducing and legitimizing their domination